2007
DOI: 10.1002/gcc.20496
|View full text |Cite
|
Sign up to set email alerts
|

ArrayCGH‐based classification of neuroblastoma into genomic subgroups

Abstract: High-resolution array comparative genomic hybridization (arrayCGH) profiling was performed on 75 primary tumors and 29 cell lines to gain further insight into the genetic heterogeneity of neuroblastoma and to refine genomic subclassification. Using a novel data-mining strategy, three major and two minor genomic subclasses were delineated. Eighty-three percent of tumors could be assigned to the three major genomic subclasses, corresponding to the three known clinically and biologically relevant subsets in neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 34 publications
12
70
0
2
Order By: Relevance
“…S1). Moreover, the CCND1 gene sporadically showed high level amplification, which is in line with our previous findings (Molenaar et al, 2003;Michels et al, 2007). In our cohort of 82 neuroblastomas, we identified two primary tumors with high level amplification of the 11q13 region including the CCND1 gene (Supporting Information Fig.…”
Section: Aberrations Of Ccnd1-cdk Complex Genes In Neuroblastomasupporting
confidence: 91%
See 1 more Smart Citation
“…S1). Moreover, the CCND1 gene sporadically showed high level amplification, which is in line with our previous findings (Molenaar et al, 2003;Michels et al, 2007). In our cohort of 82 neuroblastomas, we identified two primary tumors with high level amplification of the 11q13 region including the CCND1 gene (Supporting Information Fig.…”
Section: Aberrations Of Ccnd1-cdk Complex Genes In Neuroblastomasupporting
confidence: 91%
“…Several of these events have been reported before. We and others have reported sporadic cases of CCND1 amplification (Molenaar et al, 2003;Michels et al, 2007). CDK4 amplifications in neuroblastoma have been identified before but only in established cell lines (Van Roy et al, 1995;FAn et al, 1999).…”
Section: Discussionmentioning
confidence: 79%
“…(Cohn et al, 2009). Recent publications clearly show the potential of comprehensive genome-wide approaches to further refine the prognostic accuracy of somatically acquired chromosomal alterations, (Vandesompele et al, 2005;Michels et al, 2007;Mosse et al, 2007;Schleiermacher et al, 2007;Tomioka et al, 2008). These studies have shown that in tumours without MYCN amplification, segmental chromosome aberrations are associated with clinically aggressive disease.…”
Section: Genetic Features Of Neuroblastic Tumours Associated With Unfmentioning
confidence: 99%
“…Chip-based technologies have also been used to molecularly classify neuroblastoma tumours (Bilke et al, 2005;George et al, 2005;Selzer et al, 2005;Spitz et al, 2006;Stallings et al, 2006;Lastowska et al, 2007;Michels et al, 2007;Mosse et al, 2007;Tomioka et al, 2008). Comparative genomic hybridisation has reached a high coverage of the target sequences and become more widely used.…”
Section: Dna-based Biomarkersmentioning
confidence: 99%
“…We have previously reported high-level genomic amplification of the Cyclin D1 gene in 5 out of 202 neuroblastoma tumors and cell lines. Others also reported recurrent high-level genomic amplifications of the 11q13 region encompassing the Cyclin D1 gene (Molenaar et al, 2003;Michels et al, 2007). These clonal events clearly pointed to a crucial function for Cyclin D1 in neuroblastoma tumor genesis, but could not explain the overexpression of Cyclin D1 in about 75% of the remaining neuroblastomas, that showed Cyclin D1 expression levels reaching equal or even higher levels compared to tumors with genomic amplification.…”
Section: Introductionmentioning
confidence: 98%